(untitled) (International Journal of Scientific Trends, 2025)
Two–stage dental implantation is a modern method of restoring the dentition, in which the procedure for installing an implant is divided into two main stages. The first stage involves the surgical insertion of an implant into the jaw bone. This is followed by a waiting period, during which the osseointegration process takes place – the fusion of the implant with the bone tissue. The second stage of dental implantation begins after the successful completion of this process and includes the installation of an abutment and prosthetics – the direct restoration of the tooth crown.